Impact of motivation factors on workforce productivity in Tenaga Nasional Berhad / Muhammad Hafeez Hassan - Muhammad Hafeez, Hassan (2020)
Motivation factors are an important aspect in workforce productivity. In an organization, workforce motivation are among the main important criteria to ensure a smooth and stable business operation. The motivation of workforce will directly impact the individual, organization and team in an organization which will also influence the organizational behavior. This research aim is to investigate the impact of motivation factors on workforce productivity in Tenaga Nasional Berhad. The objectives of the research is to explore the motivation factor affecting workforce motivation, to investigate the impact of motivation factor on workforce productivity and to recommend on how to improve motivation and productivity in Tenaga Nasional Berhad. An online questionnaire survey was conducted and the target participant is the employees of TNB. This research contributes in exploring the motivation factors, the impact to workforce productivity and improvement to increase workforce motivation in TNB.